HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN - Kartika; Hamalding, Hermawati; Ismuntania; Batubara, Khairunnisa; Fazilla, Rina (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Patient satisfaction is a problem in hospitals both in Indonesia and abroad. Low patient satisfaction rates have an impact on hospital development. In patients who are dissatisfied with the health services received, one of the consequences is that patients decide to move to another hospital that can provide better services. Caring behavior is very important to be implemented in hospitals, because it can improve the quality of the relationship between nurses and patients. The purpose of this study was to determine the relationship between nurses' caring behavior and patient satisfaction levels. The research method used quantitative analytic with a cross-sectional approach. The population in this study were all patients in the cardiac inpatient room, totaling 77 people. The sampling technique used purposive sampling technique totaling 43 people. The results of the study showed that there was a relationship between nurses' caring behavior and patient satisfaction levels in the Cardiac Inpatient Room of RSUD. Tgk Chik Ditiro with a p-value of 0.004 <0.05. The conclusion in this study is that there is a relationship between nurses' caring behavior and patient satisfaction levels in the Cardiac Inpatient Room of RSUD. Tgk Chik Ditiro. Important advice for patients is to share experiences honestly and openly, both positive and those that need improvement, and to convey the patient's wishes so that nurses are able to respond to the patient's needs with caring behavior.